THE ROLE OF HR ANALYTICS IN THE PERSONNEL CONTROL SYSTEM AND HR MANAGEMENT OF THE ENTERPRISE IN MODERN BUSINESS PROCESSES - DANILKOVA, Anastasiia; SHELEST, Ievgeniia; MANTUR-CHUBATA, Olena; ZELENA, Maria (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article specifies the concepts of "personnel control" and "HR-analytics", defines the object and subject of personnel control, outlines the main directions and tasks of controlling. The article proposes the stages of formation of the controlling service at the enterprise. The study of the step-by-step implementation of the controlling service revealed that information flows play an important role in the functioning of personnel controlling, because it is the availability of valid, up-to-date information about personnel that is the key to the successful functioning of the controlling service. It was determined that HR analytics is a tool that greatly facilitates the work of the controlling service and brings it to a qualitatively new level. HR-analytics is able not only to form an information field, but also to provide analytical material that will form the basis of personnel controlling.Based on data from the HR department, HR analytics provides objective information about the real state of HR management at the company, determines what is working well and what is not, so that business entities can make the necessary adjustments in time and plan the future more effectively.In general, at enterprises, the function of collecting and processing information in most cases falls under the responsibilities of the personnel department, but the personnel department only ensures the proper processing of information, its storage, i.e., accumulates information in accordance with the requirements of current legislation. At the same time, the personnel department does not use the available information for the purpose of thorough analysis, decision-making on improving the efficiency of the use of the company's personnel, etc.The process of implementing HR analytics consists in the implementation of a certain algorithm of actions. First of all, all the necessary data is collected, then the information obtained is compared with normative indicators, which helps to determine trends or patterns, the information obtained is analyzed, and insights are then applied to organizational decisions.
Keywords: personnel controlling; HR analytics; analysis; HR management; measurement; data collection; application